Characterization and interaction of geometric and contact/impact nonlinearities in dynamical systems. (15th March 2022) - Saunders, B.E.; Vasconcellos, R.; Kuether, R.J.; Abdelkefi, A.
Highlights: How a contact/impact interacts with a geometric nonlinearity in an oscillator system is studied. Specific focus is shown to the effects on bifurcation behavior and secondary resonances. Nonlinear characterization on super- and sub-harmonic resonances and grazing is performed. Subharmonic resonance behavior is prone to multistable responses with distinct magnitudes. Contact stiffness and freeplay gap behaviors indicate the cubic nonlinearity is dominant overall. Abstract: In this work, we study how a contact/impact nonlinearity interacts with a geometric cubic nonlinearity in an oscillator system. Specific focus is shown to the effects on bifurcation behavior and secondary resonances (i.e., super- and sub-harmonic resonances). The effects of the individual nonlinearities are first explored for comparison, and then the influences of the combined nonlinearities, varying one parameter at a time, are analyzed and discussed. Nonlinear characterization is then performed on an arbitrary system configuration to study super- and sub-harmonic resonances and grazing contacts or bifurcations. Both the cubic and contact nonlinearities cause a drop in amplitude and shift up in frequency for the primary resonance, and they activate high-amplitude subharmonic resonance regions. The nonlinearities seem to never destructively interfere. The contact nonlinearity generally affects the system's superharmonic resonance behavior more, particularly with regard to the occurrence of grazing contacts and the activation of many bifurcations in the system's response. The subharmonic resonance behavior is more strongly affected by the cubic nonlinearity and is prone to multistable behavior. Perturbation theory proved useful for determining when the cubic nonlinearity would be dominant compared to the contact nonlinearity. The limiting behaviors of the contact stiffness and freeplay gap size indicate the cubic nonlinearity is dominant overall. It is demonstrated that the presence of contact may result in the activation of several bifurcations. In addition, it is proved that the system's subharmonic resonance region is prone to multistable dynamical responses having distinct magnitudes.